Individual mobility pattern in Malaysia during COVID‐19 Recovery Movement Control Order partial lockdown. Issue 1 (20th June 2022) - Ujang, Uznir; Azri, Suhaibah
Abstract: Malaysia Recovery Movement Control Order (RMCO) aims to bring the business, education, tourism and other industry sectors back into operation. Due to movement constraints that result in local economic patterns, individual mobility patterns are expected to occur. However, this matter needs further investigation from people's spatial behaviour during the RMCO. Therefore, this research proposed a new technique for analysing people's spatial behaviour patterns via geo‐tagged data. The data from social media users are gathered using data mining techniques. Geographical Information System (GIS) is used to show the geolocation of social media users and analyse their spatial behaviour. The finding of this analysis shows higher people's movement recorded when the RMCO was enforced; a distinctive pattern where spatial trajectory length is high but spatial area coverage is low. It is noticed that the focal points are concentrated in urban areas and tourism attractions. Abstract : Malaysia Recovery Movement Control Order (RMCO) aims to bring the business, education, tourism, and other industries sectors back into operation. Individual mobility patterns are expected to occur due to movement constraints that result in changes in local economic patterns. However, this matter needs further investigation from the perspective of people's spatial behavior during the RMCO. Therefore, this research proposed a new technique in analyzing people's spatial behavior patterns via geo‐tagged data. The data from social media users is gathered using the data mining techniques. Geographical Information System (GIS) is used to show the geo‐location of social media users and analyse their spatial behavior. The finding of this analysis shows higher people's movement recorded when the RMCO was enforced. Distinctive pattern where spatial trajectories length is high but spatial area coverage is low. It is noticed that the focal points are concentrated in urban areas and tourism attractions.